The impact of the use of Information and Communication Technologies (ICTs) by teachers at the Federal Institutes located in Minas Gerais Gerais in a pandemic context (Research, Society and Development, 2020)
In view of the pandemic caused by the new coronavirus (SARS-CoV-2), several segments had their face-to-face activities suspended, including schools. To create opportunities for the continuity of curricular activities, a new teaching model has emerged: emergency remote education. In this study, a descriptive and quantitative research was carried out, considering information obtained through an online questionnaire for all professors at Federal Institutes (FI’s) in the state of Minas Gerais. The objective of the research was to evaluate the use of Information and Communication Technologies (ICTs) by teachers of FI’s in Minas Gerais and the impact of their use (or not) in remote education during the pandemic caused by the coronavirus. In general, it was observed that this period has been one of adaptation and learning in the handling of these technologies for both teachers and students. Despite the various difficulties presented by teachers in relation to remote education during the pandemic, a very positive scenario can be seen in relation to both face-to-face and remote teaching in relation to the use of ICTs, even after the pandemic. However, there is still a need for assessment and adequacy of current remote education mediated by ICTs in formats that guarantee an effective learning.